Development of Depotentiation in Adult-Born Dentate Granule Cells - Tao, Xiaoqing; Sun, Ning; Mu, Yangling (Frontiers in Cell and Developmental Biology, 2019)
Activity-dependent synaptic plasticity, i.e., long-term potentiation (LTP), long-term depression (LTD) and LTP reversal, is generally thought to make up the cellular mechanism underlying learning and memory in the mature brain, in which N-methyl-D-aspartate subtype of glutamate (NMDA) receptors and neurogenesis play important roles. LTP reversal may be the mechanism of forgetting and may mediate many psychiatric disorders, such as schizophrenia, but the specific mechanisms underlying these disorders remain unclear. In addition, LTP reversal during the development of adult-born dentate gyrus cells (DGCs) remains unknown. We found that the expression of the NMDA receptor subunits NR2A and NR2B displayed dynamic changes during the development of postnatal individuals and the maturation of adult-born neurons and was coupled with the change in LTP reversal. The susceptibility of LTP reversal progressively increases with the rise in the expression of NR2A during the development of postnatal individual and adult-born neurons. In addition, NMDA receptor subunits NR2A, but not NR2B, mediated LTP reversal in the DGCs of the mouse hippocampus.